2020
DOI: 10.21470/1678-9741-2019-0377
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Concentration of Interleukin-35 and FoxP3 Polymorphism in Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Objective To investigate the association between interleukin-35 (IL-35) levels and single nucleotide polymorphisms (rs3761548, rs3761547) of the FoxP3 gene in coronary artery bypass grafting (CABG) patients. Methods We conducted a prospective study including 140 patients, who were scheduled for elective isolated on-pump CABG with cardiopulmonary bypass (CPB) from January 2017 to September 2018 in the Jorjani heart center. Blood samples were collected before and 12 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Although, as the first report in this field, there is a need to be suitably cautious in interpreting, the lack of post‐surgery association between rs9017 genotypes and IL‐17 serum level may attribute to a post‐CPB complex interplay of humoral and cellular components of the immune system 38 . Previous studies reported the concurrence of inflammation and immune‐depression during and after CPB, resulting in extensive cytokine production alteration, including tumor necrosis factor‐α, IL‐6, and IL‐8, and transforming growth factor‐β (TGF‐β) 39–41 . Third, the RORγt expression in cells other than Th17 cells 42 such as type 3 innate lymphoid cells (ILC3s), NKT cells, and Tγδ cells, 42 may justify the protective effect of the rs9017 A allele in CPB‐AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Although, as the first report in this field, there is a need to be suitably cautious in interpreting, the lack of post‐surgery association between rs9017 genotypes and IL‐17 serum level may attribute to a post‐CPB complex interplay of humoral and cellular components of the immune system 38 . Previous studies reported the concurrence of inflammation and immune‐depression during and after CPB, resulting in extensive cytokine production alteration, including tumor necrosis factor‐α, IL‐6, and IL‐8, and transforming growth factor‐β (TGF‐β) 39–41 . Third, the RORγt expression in cells other than Th17 cells 42 such as type 3 innate lymphoid cells (ILC3s), NKT cells, and Tγδ cells, 42 may justify the protective effect of the rs9017 A allele in CPB‐AKI.…”
Section: Discussionmentioning
confidence: 99%